Dental Service Utilization, Dental Health Production and Equity in Dental Care : the Finnish Experience - Nguyen, Lien (Helsingin yliopisto, 2010)
This thesis is grounded on four articles. Article I generally examines the factors affecting dental service utilization. Article II studies the factors associated with sector-specific utilization among young adults entitled to age-based subsidized dental care. Article III explores the determinants of dental ill-health as measured by the occurrence of caries and the relationship between dental ill-health and dental care use. Article IV measures and explains income-related inequality in utilization. Data employed were from the 1996 Finnish Health Care Survey (I, II, IV) and the 1997 follow-up study included in the longitudinal study of the Northern Finland 1966 Birth Cohort (III). Utilization is considered as a multi-stage decision-making process and measured as the number of visits to the dentist. Modified count data models and concentration and horizontal equity indices were applied. Dentist s recall appeared very efficient at stimulating individuals to seek care. Dental pain, recall, and the low number of missing teeth positively affected utilization. Public subvention for dental care did not seem to statistically increase utilization. Among young adults, a perception of insufficient public service availability and recall were positively associated with the choice of a private dentist, whereas income and dentist density were positively associated with the number of visits to private dentists. Among cohort females, factors increasing caries were body mass index and intake of alcohol, sugar, and soft drinks and those reducing caries were birth weight and adolescent school achievement. Among cohort males, caries was positively related to the metropolitan residence and negatively related to healthy diet and education. Smoking increased caries, whereas regular teeth brushing, regular dental attendance and dental care use decreased caries. We found equity in young adults utilization but pro-rich inequity in the total number of visits to all dentists and in the probability of visiting a dentist for the whole sample. ...